Design and Experiment for Dual-Mass MEMS Gyroscope Sensing Closed-Loop System - Huiliang Cao; Rihui Xue; Qi Cai; Jinyang Gao; Rui Zhao; Yunbo Shi; Kun Huang; Xingling Shao; Chong Shen (IEEE Access, 2020)
A closed-loop controlling system for Micro Electro Mechanical System (MEMS) gyroscope sense mode is investigated in this paper, and the controller is designed to achieve low error, wide bandwidth and low noise capability. The gyroscope monitoring system includes four independent closed-loop, and is simulated by Simulink soft to prove the speedability and stability of the sensing closed-loop. The gyroscope monitoring system is realized through 3 analog circuit boards, and is tested through temperature controlled turntable. The bias stability, angular random walking value and bias temperature coefficients improved from 2.168 °/h, 0.155°/√h and 10.59 °/h/°C to 0.415 °/h, 0.0414°/√h and 3.59°/h/°C. And the bandwidth value is improved from 13Hz to 104Hz. Meanwhile, scale factor nonlinearity, asymmetry, repeatability and temperature coefficient parameters are enhanced from 660 ppm, 430ppm, 403ppm and 180 ppm/°C to 59.3ppm, 62.4ppm, 50.4ppm and 28.7 ppm/°C respectively.